Pemanfaatan Bubuk Kopi Sebagai Antimikroba pada Pembuatan Sabun - Nurul Lailatul; Mohammad Rony; Aditya Stenno Putra Pamungkas; Indri Ilmiyatul Hasanah; Habibah Ayu Al Faiza; Rizka Alvina Rachmawati; Muhammad Rafli Isla Nandika; Bunga Fadia Sukmawati; Indah Rahayu; Hani Urrohmah; Ayu Dwi Lestari (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2022)
Coffee (Coffea spp. L.) is one of the annual plants cultivated in Indonesia and is included in the strategic category. One of the areas for developing coffee plantations in East Java Province is located in Jember Regency with the greatest potential in Pace Village. Robusta coffee cultivation in Pace Village is developed to the post-harvest stage. One of the post-harvest activities for robusta coffee developed by the Women Farmers Group (KWT) is product innovation. The purpose of this research is to create an innovative dish soap product made from robusta coffee powder as an output in the service of Real Work Lectures (KKN) in 2022. The method used in this study is a qualitative research method. Based on the results of the study, the presence of dish soap is the result of an agro-industrial product with a brown color and a slightly thick texture. The coffee product agroindustry is expected to improve the economy of the Pace Village community and increase the Pace community's ability to process coffee products so that they do not depend on coffee middlemen.